THE INFLUENCE OF COMPENSATION, WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE OF PT. YAMAHA THAMRIN BROTHERS LEBONG - Agustian, Muhammad Ryan Fero; Markoni, Markoni; Armi, Muhammad Noor (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
This research determine how much influence compensation, work environment organizational culture have performance PT employees. Yamaha Thamrin Brothers Lebong. research sample 20 respondents were employees at PT. Yamaha Thamrin Brothers Lebong, research multiple linear regression analysis methods collecting data questionnaires Likert determination scales, t tests and F tests. Results data processing linear regression calculations Y = 1,002 = 0.652X1 + 0.583X2 + 1.052X3 + e . R Square Multiple Determination Coefficient is 0.964, means 96.4%. From the results t test, the calculated t value for the compensation variable (X1) is 2.901 with α = 0.010 < α = 0.05, this means that H0 is rejected and Ha is accepted, so the compensation variable influence on employee performance (Y). The calculated t value organizational culture variable (X2) is 2.558 with α = 0.021 < α = 0.05, this means H0 is rejected and Ha is accepted, organizational culture variable influence on employee performance (Y). The calculated t value for the work environment variable (X2) is 16.479 with α = 0.001 < α = 0.05, this means that H0 is rejected and Ha is accepted, so the work environment variable has an influence on employee performance (Y). From the results F test, the calculated F is 196.693 with α = 0.001 < α = 0.005, this means that H0 is rejected and Ha is accepted. Overall, is an influence compensation, work environment and organizational culture on the performance of PT employees. Yamaha Thamrin Brothers Lebong.